2003
DOI: 10.1017/s1446788700003505
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Point Methods and Banach-Stone Theorems

Abstract: An operator is said to be nice if its conjugate maps extreme points of the dual unit ball to extreme points. The classical Banach-Stone Theorem says that an isometry from a space of continuous functions on a compact Hausdorff space onto another such space is a weighted composition operator. One common proof of this result uses the fact that an isometry is a nice operator. We use extreme point methods and the notion of centralizer to characterize nice operators as operator weighted compositions on subspaces of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…The result (1) follows the same line of reasoning as previous results [1,6,18,25,28]. On the other hand, (2) and (3) seem to exhibit a relatively new variant in that their assumptions are involved in the topology of underlying spaces X and Y (see [33] and a paper by K. Kawamura and Miura, 'Real-linear surjective isometries between function spaces,' which has been submitted for publication).…”
Section: Introductionsupporting
confidence: 69%
“…The result (1) follows the same line of reasoning as previous results [1,6,18,25,28]. On the other hand, (2) and (3) seem to exhibit a relatively new variant in that their assumptions are involved in the topology of underlying spaces X and Y (see [33] and a paper by K. Kawamura and Miura, 'Real-linear surjective isometries between function spaces,' which has been submitted for publication).…”
Section: Introductionsupporting
confidence: 69%
“…Such operators have been studied in the literature. See [1,2,4,7,10,14,15,21,22,24,27,29,30] and [25] for more recent results.…”
Section: Introductionmentioning
confidence: 99%
“…The general question to be asked, then, is the converse: if T ∈ L(X, Y ) is extreme, must it be nice? The answer, in general, is no, since it has been shown that there exists a four-dimensional Banach space X and an extreme contraction T from X to C [0,1] that is not nice [2]. However, there is a positive answer for certain C(K) spaces, as we have already mentioned above, and other versions of the BLP result have been given by several authors.…”
Section: T F(t) = H(t)f (ϕ(T))mentioning
confidence: 96%
“…This form is typical of nice operators on continuous function spaces, even in the vector-valued case [1].…”
Section: T F(t) = H(t)f (ϕ(T))mentioning
confidence: 98%